Die auswärtige Gewalt des Europäischen Parlaments : Kritik der Legitimation und Dogmatik der außenpolitischen Prärogative der Exekutive = The foreign policy power of the European Parliament : a critique of the legitimacy and doctrinal conception of the executive prerogative in foreign affairs /: Kritik der Legitimation und Dogmatik der außenpolitischen Prärogative der Exekutive = The foreign policy power of the European Parliament : a critique of the legitimacy and doctrinal conception of the executive prerogative in foreign affairs. ([2018]) - Sangi, Roya
No abstract available